(untitled) (Medical Forum Monthly, 2020)
Objective: To compare the effectiveness in term of stone clearance between ureterolithotripsy, extracorporeal shock wave lithotripsy and Laparoscopic Ureterolithotomy. Study Design: Comparative study Place and Duration of Study: This study was conducted at the Urology Department Sandeman Civil Hospital Quetta, from April 2019 to June 2020. Materials and Methods: In this study, 80 patients of both genders having large stones (>1cm) in proximal ureter were included. After taking informed consent, patient’s detailed history including age, sex and BMI were recorded. 24 patients received ureterolithotripsy, 27 patients received extracorporeal shock wave lithotripsy, and 29 patients received laproscopicuretrolithotomy treatment. Effectiveness in term of stone clearance was recorded and compared between treatment procedures. Data was analyzed by SPSS 24.0. Results: There were 46 (57.50%) males while 34 (42.50%) females patients with mean age 37.26±10.54 years. Mean BMI was 23.43±2.05 kg/m2. Extracorporeal shock wave ithotripsy had significantly shorter operative time 40.85±4.62 minutes as compared to uretrolithotripsy and laparoscopic uretrolithotomy 68.72±5.22 minutes and 110.06±11.38 minutes (p-value <0.05). Patients received laparoscopic uretrolithotomy had significantly higher stone clearance rate 93.10% as compared to extracorporeal shock wave lithotripsy and uretrolithotripsy 55.56% and 58.33% (p-value <0.05). Conclusion: Laparoscopic uretrolithotomy was more effective than extracorporeal shock wave lithotripsy and uretrolithotripsy in term of stone clearance.